GOOD GOVERNANCE VILLAGE FINANCIAL MANAGEMENT APPROACHING THE ENACTMENT OF UU NO. 6 YEAR 2014 - Titiek Puji Astuti; Yulianto Yulianto (Universitas Airlangga, 2016)
It is estimated that all villages in Indonesia will receive transfer funds from the State Revenue and Expenditure Budget (APBN). Each village, which currently amounts to 72 thousand throughout Indonesia, will receive a budget ranging from Rp 800 million to Rp 1.4 billion per village. Therefore, it is necessary to have good governance in managing village finances. Good Governance is proposed to achieve more transparent management for all uses of financial statements. This research was conducted using a case study method, namely, detailed observations of objects or people. The research locations selected as case studies are villages in Polokarto District, Sukoharjo, Central Java. The analysis technique used is analytic logic. The results of this study are the existence of transparency, accountability and participation in village financial management because it is an important aspect in creating good governance in village financial management which has been stated in Law No. 14 on Villages. Barriers to the implementation of good governance in village financial management are incompetent human resources in the village government.